The Phenomenon of primary and secondary animals within Iron Age deposits. - Bangsgaard, Pernille; Pantmann, Pernille (Danish Journal of Archaeology, 2022)
Animals are an integral part of deposition practices during the Danish Iron Age, and they probably represent the most common form of deposit within southern Scandinavia. Recently Gotfredsen published a volume on animals within Danish Iron Age grave contexts, but similarly comprehensive studies of animals from other contexts have not been attempted. Thus, classic sites such as Valmose, Bukkerup Langmose, and Sorte Muld still stand as the type sites for Danish Iron Age animal deposits. This article will demonstrate that there are good reasons for exploring deposits in more detail and investigate the significant variation in the treatment and quantities of sacrificial animal deposits. Furthermore, the current study has revealed a deposition pattern where a primary animal is often in the company of one or more secondary animals, the latter typically represented by a few bones. Salpetermosen Syd (MNS50010), south of Hillerød in North Zealand, Denmark is the main case study, but comparisons are made to several sites across Denmark where a similar deposition pattern has been observed.